POLITICAL PARTICIPATION DISABILITIES VOTERS IN SIMULTANEOUS ELECTION 2019 IN SUB-DISTRICT OF CIJULANG, DISTRICT OF PANGANDARAN: Array - Chintia Stratawanti Sunarya; Aditiyawarman; Aan Anwar Sihabudin (JGSRD: Journal of Government Science and Rural Development, 2021)
Background of this research is unreachable accessibility to polling station for disabilities voters due to considerable distance from residence and poor political awareness themselves; Formulation of the problems: How is the political participation of disabilities voters in general election 2019 at Sub-district of Cijulang, District of Pangandaran? What are the obstacles that can affect the political participation of disabilities voters in Sub-district of Cijulang, District of Pangandaran? What are the efforts that made by the committee to increase the political participation of disabilities voters at Sub-district of Cijulang, District of Pangandaran? How can the efforts made by the committee of voters to increae the political participation of disabilities voters in the Sub-district of Cijulang, District of Pangandaran? This research used qualitative method. Conclusions of the result of this research are: Generally, political participation of disabilities voters in Simultaneous Election 2019 at Sub-district of Cijulang, District of Pangandaran has been implemented. The obstacles that can affect political participation of disabilities voters at Sub-district of Cijulang, District of Pangandaran are: Unavailability of capable and skilled person in dealing with disabilities voters, limited time that has of PPK and limited supporting facilities, insufficient of component, there is no party that involving disabilities voters and the effort that made by the committee to increase the political participation of disabilities voters at Sub-district of Cijulang, District of Pangandaran that is recruiting people who are able to deal with disabilities, approaching and communicating with disabilities, allocating time for, assigning component specifically, and asking political parties to involve disabilities voters.